Means of communication of new religious movements in the Republic of Belarus - Martinovich, Vladimir A. (Journal of the Belarusian State University. Sociology, 2021)
This article is devoted to the analysis of the means of communication of new religious movements in the Republic of Belarus. Due to the high level of closeness of the overwhelming number of new religions for questioning, interviews, observation and experiment, their means of communication with society are the most accessible documentary source of primary sociological information for research. As part of the monitoring of the confessional space of the country, conducted since 1997, information was collected on 1113 new religious movements. The means of communication used by them to broadcast religious ideas and teachings, including in the public space of the Republic of Belarus, are documented. A number of methodological problems related to the analysis of the means of communication of new religious movements are identified. The frequency of appeals of new religions to print media, the Internet, leaflets, books and specialised periodicals has been established. The entire set of means, depending on the target audience, is divided into internal, external and universal. The degree of informativeness of external and universal means of communication for scientific analysis, is analysed. It is noted that the openness of the new religious movements to society, which implies the disclosure of a significant part of their internal information, does not automatically mean recognition and acceptance of society, readiness for a constructive dialogue with it. The connection between the type of structure of the new religious movements and the number of different means of communication used by them is revealed. The minimum provable number of new religious movements working in the public space through means of communication accessible to the general population has been established.